Analisis Tingkat Pemahaman Masyarakat di Desa Batu Bandung Kecamatan Pino Kabupaten Bengkulu Selatan Terhadap Lembaga Keuangan Mikro Syariah - Rahina, Kinanti Shely; Idwal, Idwal; Setiawan, Adi (Prodi Perbankan Syariah FAI UMT, 2024)
The aim of this research is to determine the understanding of the community in Batu Bandung Village, Pino District, South Bengkulu Regency towards sharia microfinance institutions. The research method uses descriptive using a qualitative approach. The results of the research show that the people of Batu Bandung Village, Pino District, South Bengkulu Regency do not understand the difference between conventional microfinance institutions and sharia microfinance institutions. The community's understanding of Batu Bandung Village, Pino District, South Bengkulu Regency regarding products at sharia microfinance institutions is only limited to fund distribution products such as murabahah and musyarakah financing, while other products such as murabahah savings, wadiah savings, bai'u bithaman ajil financing, financing ajil is not yet understood. The understanding of the people of Batu Bandung Village, Pino District, South Bengkulu Regency regarding contracts in sharia financial institutions is only limited to knowing murabah and musyarakah contracts, while other contracts such as qardh contracts, salam contracts, mudharabah contracts, ijarah contracts, jua’alah contracts and hiwalah contracts are not understood.